DEVELOPMENT OF WAYS TO ADAPT AGRICULTURAL ENTERPRISES TO CHANGES IN THE MARKETING COMPETITIVE ENVIRONMENT - Mariia Bahorka; Liudmila Kvasova; Nataliy Yurchenko (Izdevnieciba "Baltija Publishing", 2023)
The purpose of the article is the generalisation of research methods in the marketing information system of the environment, the practical implementation of the procedure of researching the competitive environment of an agricultural enterprise, and the development of ways of adapting agricultural enterprises to changes in the competitive marketing environment. The main methods of marketing research based on information analysis and forecasting are summarized. Results. The article summarises research methods in the marketing information system of the environment, presents the procedure for researching the competitive environment of an agricultural enterprise, and suggests ways of adapting agricultural enterprises to changes in the marketing competitive environment. Practical results. The need for adaptation of agricultural enterprises to dynamic changes occurring in the socio-economic environment is established, with specific measures of organisation of work on the formation and promotion of sales of the marketing structure of the enterprise and ways of adaptation of agricultural enterprises to changes in the marketing competitive environment. Value/originality. The prerequisites for the formation of competitive factors of companies are constantly changing. Within the framework of this research, the main types of such changes have been summarised and tasks have been identified that will help companies adapt to the competitive marketing environment.